More socially responsible, more ethical, more attractive as a future employer? Contributes of corporate social performance and ethical reputation for the attraction of future employees - Duarte, A. P.; Silva, V. H.; Simões, E.; Neves, J. G. das. (Atas do IX Simpósio Nacional de Investigação em Psicologia, 2017)
Previous studies suggest that the corporate social performance of organizations influences their attractiveness as a workplace. This study analyzed additional variables that may help explain this relationship. In this context, an ethical reputation is a construct positively related to corporate social responsibility (CSR). In the research, CSR perception was manipulated in order to observe its effect on organizational attractiveness through the mediating effect of ethical reputation. Participants (n = 260) were randomly subjected to two experimental conditions by responding to an electronic questionnaire containing the description of an organization that implements (i.e., the high involvement condition) or not (i.e., the low involvement condition) a set of CSR practices. This was followed by questions about other variables of interest. The results show that the proposed theoretical model provides a strong fit to the data, thus empirically supporting the proposal that CSR directly and indirectly affects, through ethical reputation, evaluations of organizations as a future workplace. In practical terms, this means that, in the war for talent, organizations can use information about their corporate social performance and ethical reputation to attract potential candidates, alongside more traditional information on organizational attributes and job characteristics.